Activated Carbon for Drug Delivery from Composite Biomaterials: The Effect of Grinding on Sirolimus Binding and Release - Zhanna K. Nazarkina; Tatyana A. Savostyanova; Boris P. Chelobanov; Irina V. Romanova; Pavel A. Simonov; Ren I. Kvon; Andrey A. Karpenko; Pavel P. Laktionov (MDPI AG, 2022)
Activated carbon (AC) could be potentially useful as a drug carrier in fiber polymer scaffolds destined for prolonged drug delivery. To be introduced, AC must be ground into smaller-sized particles to be introduced in scaffolds, as most biocompatible scaffolds consist of fibers with a diameter of less than 1 µm. In this study, the adsorption of sirolimus (SRL) from phosphate-buffered saline (PBS) solution and blood plasma (BP) onto AC of AX-21 type, as well as the release of SRL from AC depending on its fragmentation, were studied. Two-stage grinding of the AC, first with a ball mill, and then with a bead mill, was performed. Grinding with a bead mill was performed either in water or in polyvinylpyrrolidone to prevent aggregation of AC particles. Dynamic light scattering and scanning electron microscopy (SEM) demonstrated that the size of the particles obtained after grinding with a ball mill was 100-10,000 nm, and after grinding with a bead mill, 100-300 nm. Adsorption in PBS was significantly higher than in BP for all fractions, and depended on SRL concentration. The fraction obtained after grinding with a ball mill showed maximal SRL adsorption, both in PBS and BP, and slow SRL release, in comparison with other fractions. The 100-300 nm AC fractions were able to adsorb and completely release SRL into BP, in contrast to other fractions, which strongly bound a significant amount of SRL. The data obtained are to be used for controlled SRL delivery, and thus in the modification of drug delivery in biological media.